Teacher Understanding on the Implementation of Curriculum 2013 in Using Learning Models in Vocational High School, Banda Aceh, Indonesia - Razali, Fadhilah (International Journal of Scientific Research and Management (IJSRM), 2018)
This paper is triggered by the issue of curriculum 2013. As a curriculum change, creativity and independence of the teacher are the major issue in implementing curriculum 2013. Teachers should have high competence in carrying out professional duty. Thereby, curriculum 2013 is directed to improve the capacity of teacher in achieving the objective of teaching.  However, to ensure curriculum 2013 can be implemented  effectively, it is important to determine teacher understanding in using learning model. Therefore, the objective of this paper is to analyze the teachers' understanding on implementation of curriculum 2013 in using learning models. It is expected that curriculum 2013 will support objective of  Vocational High School in Banda Aceh, Indonesia in yielding qualified graduates in order to anticipate competition in today’s working environment.